2012
DOI: 10.1111/j.1745-4557.2012.00452.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Characterization of Sicilian Yellow Flesh Peach (Prunus persicaL.) Cultivars at Different Ripening Stages

Abstract: Yellow flesh peaches (Prunus persica L.) from different Sicilian areas (Leonforte, Riesi and Maniace) were investigated for the first time for their polyphenolic composition, with consideration of both peel and flesh tissues. The qualitative and quantitative polyphenolic evaluation was determined at two different maturity stages (commercial and postharvest ripening) via chromatographic separation by using reverse‐phase HPLC‐PDA‐ESI/MS 2. This technique provides a comprehensive chromatographic evaluation of 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
22
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 21 publications
11
22
0
1
Order By: Relevance
“…The contents of kaempferol-3-rutinoside were in the range of 2.8 to 15.0 mg kg -1 f.w. Scordino et al (2012) gave similar values (3.7-12 mg kg -1 f.w.). Previous studies have only shown quercetin derivatives (Tomas-Barberan et al, 2001;Cantin et al, 2009;Orazem et al, 2011).…”
Section: +supporting
confidence: 65%
See 3 more Smart Citations
“…The contents of kaempferol-3-rutinoside were in the range of 2.8 to 15.0 mg kg -1 f.w. Scordino et al (2012) gave similar values (3.7-12 mg kg -1 f.w.). Previous studies have only shown quercetin derivatives (Tomas-Barberan et al, 2001;Cantin et al, 2009;Orazem et al, 2011).…”
Section: +supporting
confidence: 65%
“…CevallosCasals et al (2006) also reported that contents of phenolic compounds vary within different tissues of the same fruits and are mostly concentrated in the epidermal and subepidermal layers of the fruits. Higher concentrations of TF compounds in peach peel compared to the pulp were also reported by other researchers (Tomas-Barberan et al, 2001;Scordino et al, 2012). The effect of acidified solvents on the extraction of the peach phenolics was evaluated using aqueous HCl in 80% acetone as the solvent.…”
Section: Total Flavonoidsmentioning
confidence: 74%
See 2 more Smart Citations
“…It is commonly known as "Aaru" and in English popularly called "Peach" has been extensively consumed worldwide.Peach has an important place in human nutrition, and can be used as fresh, dried or processed fruit.Peaches (Prunus persica (L.) Batsch) are nutritionally and economically essential and they are one of the most popular fruits consumed worldwide [21], [47]. Different phenolic compounds have been recognized in peach fruits [29], [55] Table III Some economically important species of subfamily amygyloideae (2) . It is deciduous tree up to 10m in height [16] or evergreen trees and shrubs naturally distributed throughout temperate regions, originally from Asia or Southern Europe [16], [22].Generally, its bark is grayish or ashy acuminate glabrous [16], [18].…”
Section: A Prunus Persica (Peach and Nectarine)(table Iv): Morphologmentioning
confidence: 99%